2003
DOI: 10.1074/jbc.m205006200
|View full text |Cite
|
Sign up to set email alerts
|

Stabilization Versus Inhibition of TAFIa by Competitive Inhibitors in Vitro

Abstract: Two competitive inhibitors of TAFIa (activated thrombin-activable fibrinolysis inhibitor), 2-guanidinoethylmercaptosuccinic acid and potato tuber carboxypeptidase inhibitor, variably affect fibrinolysis of clotted human plasma. Depending on their concentration, the inhibitors shortened, prolonged, or had no effect on lysis in vitro. The inhibitor-induced effects were both tissuetypeplasminogenactivator(tPA)andTAFIaconcentrationdependent. Inhibitor-dependent prolongation was favored at lower tPA concentrations.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
57
0

Year Published

2004
2004
2013
2013

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 55 publications
(62 citation statements)
references
References 29 publications
(40 reference statements)
5
57
0
Order By: Relevance
“…TAFI constitutes a risk factor for thrombosis and coronary artery disease, and its inhibition leads to an enhancement of clot lysis (40,41). The doubleheaded architecture provides TCI with a 5-fold lower K i toward TAFI compared with potato carboxypeptidase inhibitor and a 10-fold acceleration of fibrinolysis with respect to this singleheaded inhibitor used as a model in thrombolytic assays (42,43). In this way, and as previously discussed, the Nt domain could also contribute to improve the affinity/modulate the specificity of TCI toward CPBs, constituting a good target for the design of new TCI molecules to be used as thrombolytic drugs.…”
Section: Discussionmentioning
confidence: 99%
“…TAFI constitutes a risk factor for thrombosis and coronary artery disease, and its inhibition leads to an enhancement of clot lysis (40,41). The doubleheaded architecture provides TCI with a 5-fold lower K i toward TAFI compared with potato carboxypeptidase inhibitor and a 10-fold acceleration of fibrinolysis with respect to this singleheaded inhibitor used as a model in thrombolytic assays (42,43). In this way, and as previously discussed, the Nt domain could also contribute to improve the affinity/modulate the specificity of TCI toward CPBs, constituting a good target for the design of new TCI molecules to be used as thrombolytic drugs.…”
Section: Discussionmentioning
confidence: 99%
“…Plasma in Vitro Clot Lysis Assays-Clot lysis assays were performed essentially as described previously (29,30). In short, human plasma, diluted 1:3 in 20 mM Hepes, 150 mM NaCl, pH 7.4, was added to 96-well microtiter plates.…”
Section: Matrix-assisted Laser Desorption Ionization Mass Spectrometrmentioning
confidence: 99%
“…13,14 Thermal stability of TAFIa is increased by binding of small peptide substrates, like hippuryl-arginine, 15 or carboxypeptidase inhibitors such as 2-guanidino-ethyl-mercaptosuccinic acid (GEMSA). 16,17 In addition, extensive mutagenesis studies have identified 5 mutations (S305C, T325I, T329I, H333Y, and H335Q) which, in combination, stabilize TAFIa activity 180-fold. [18][19][20] In this paper we present crystal structures of wild-type TAFI, a TAFI-inhibitor complex, and a TAFI mutant with a 70-fold more stable active enzyme.…”
Section: Introductionmentioning
confidence: 99%